Notq --> not p
I am not certain you can do this
q-->p as it is a logical fallacy.
Write the statement in symbols using the p and q given below. Then construct a truth table for the symbolic statement and select the best match.
q = The food is good.
p = I eat too much.
If the food is not good, I won't eat too much.
2 answers
~q = the food is not good
~p = I won't eat too much
~q -> ~p = If the food is not good, then I won't eat too much.
q. p. ~q. ~p. ~q -> ~p
T. T. F. F. T
T. F. F. T. T
F. T. T. F. F
F. F. T. T. T
"select the best match" -- I don't know what to do with that.
~p = I won't eat too much
~q -> ~p = If the food is not good, then I won't eat too much.
q. p. ~q. ~p. ~q -> ~p
T. T. F. F. T
T. F. F. T. T
F. T. T. F. F
F. F. T. T. T
"select the best match" -- I don't know what to do with that.